Postspaceflight orthostatic hypotension occurs mostly in women and is predicted by low vascular resistance - Waters, Wendy W; Ziegler, Michael G; Meck, Janice V (Journal of applied physiology (1985), 2002)
1  National Space Biomedical Research Institute, Baylor College of Medicine, Houston, Texas 77030; 2  Department of Medicine, University of California, San Diego, California 92103; and 3  Space Life Sciences Research Laboratories, National Aeronautics and Space Administration Johnson Space Center, Houston, Texas 77058 About 20% of astronauts suffer postspaceflight presyncope. We studied pre- to postflight (5- to 16-day missions) cardiovascular responses to standing in 35 astronauts to determine differences between 1 ) men and women and 2 ) presyncopal and nonpresyncopal groups. The groups were presyncopal women, presyncopal men, and nonpresyncopal men based on their ability to stand for 10 min postflight. Preflight, women and presyncopal men had low vascular resistance, with the women having the lowest. Postflight, women experienced higher rates of presyncope (100 vs. 20%; P  = 0.001) and greater losses of plasma volume (20 vs. 7%; P  < 0.05) than men. Also, presyncopal subjects had lower standing mean arterial pressure (P   0.001) and vascular resistance ( P  < 0.05), smaller increases in norepinephrine ( P    0.058) and greater increases in epinephrine ( P  0.058) than nonpresyncopal subjects. Presyncopal subjects had a strong dependence on plasma volume to maintain standing stroke volume. These findings suggest that postflight presyncope is greatest in women, and this can be ascribed to a combination of inherently low-resistance responses, a strong dependence on volume status, and relative hypoadrenergic responses. Conversely, high vascular resistance and postflight hyperadrenergic responses prevent presyncope. microgravity; gender; sympathetic; plasma volume; vascular resistance